If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8 = 5x + (10) Reorder the terms: -8 + 2x = 5x + (10) -8 + 2x = 5x + 10 Reorder the terms: -8 + 2x = 10 + 5x Solving -8 + 2x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -8 + 2x + -5x = 10 + 5x + -5x Combine like terms: 2x + -5x = -3x -8 + -3x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 -8 + -3x = 10 + 0 -8 + -3x = 10 Add '8' to each side of the equation. -8 + 8 + -3x = 10 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = 10 + 8 -3x = 10 + 8 Combine like terms: 10 + 8 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| -12=5k-8 | | 4b-2b=20 | | x^2-30y+352=0 | | 4x+52=4(2x+8) | | 8y+7y=-75 | | (5x+1)(2x)= | | 2x+3=7x+(-42) | | 5x^4-12x^2+3=0 | | 3k=5k+7 | | -11+3x=x-15 | | 4.905x^2-4x-22=0 | | 2x^2-1528x+2821=0 | | 5p+14=29 | | m/4=2 | | 8r^2-6r-9=0 | | 9x-4=5x+32 | | 2-4x=12+x | | 5x-7=-4x+-25 | | 6(x+2)=60-6x | | 3-10=2+32 | | -2x+3x=-6x+13x | | 12/23*2/4*(11/12-5/18) | | 4x-7=-9x+84 | | 24x+38=14x | | 5v+9=33 | | 42/7a | | (4x+1)(7x-6)=0 | | 5x^2-7+2=0 | | 9x+1=3x+31 | | (2x+4)*(x-1)-36=0 | | 180x^4-108x^3-107x^2+36x+20=0sol | | 4x=46-10 |